Protein Phosphorylation Dynamics: Unexplored Because of Current Methodological Limitations: Dynamics of Processive Phosphorylation. (27th February 2020) - Robichon, Alain
Abstract: The study of intrinsic phosphorylation dynamics and kinetics in the context of complex protein architecture in vivo has been challenging: Method limitations have prevented significant advances in the understanding of the highly variable turnover of phosphate groups, synergy, and cooperativity between P‐sites. However, over the last decade, powerful analytical technologies have been developed to determine the full catalog of the phosphoproteome for many species. The curated databases of phospho sites found by mass spectrometry analysis and the computationally predicted sites based on the linear sequence of kinase motifs are valuable tools. They allow investigation of the complexity of phosphorylation in vivo, albeit with strong discrepancies between different methods. A series of hypothetical scenarios on combinatorial processive phosphorylation is proposed that are likely unverifiable with current methodologies. These proposed a priori postulates could be considered as possible extensions of the known schemes of the activation/inhibition signaling process in vivo. Abstract : The intracellular transduction pathways triggered by exogenous signaling inputs activate the phosphorylation of target proteins. The linear consensus motifs of kinases substrates are only partly informative regarding the vivo phosphorylation events. Few hypotheses among a large spectrum of possibilities are discussed to approach the complexity and dynamics of phosphorylation that control the biological systems.